Swedish electoral data: General election 1976 - Statistics Sweden (Statistics Sweden, 1989)
Election returns for all electoral districts in Sweden. Includes information on the total number of persons entitled to vote in the general election, number of persons who actually voted, and number of valid and invalid ballots respectively. The number of votes casted by postal voting is also included.

Valresultat för samtliga valdistrikt vid riksdagsvalen 1973-2006. Innehåller uppgifter om det totala antalet röstberättigade, antal röstande, antal giltiga respektive ogiltiga valsedlar samt antalet poströster. Dessutom finns uppgifter om antalet röster för de större partierna.
Svenska valdata: Riksdagsvalet 1976
Keywords: elections; val; parliamentary elections; riksdagsval; election data; valdata; Elections; Val; Social Sciences; Samhällsvetenskap